Quantitative analysis of black blotching in a crossbred red tilapia and its effects on performance traits via a path analysis methodology - de Assis Lago, Aline; Reis-Neto, Rafael Vilhena [UNESP]; Rezende, Tiago Teruel; da Silva Ribeiro, Mayra Cristina; de Freitas, Rilke Tadeu Fonseca; Hilsdorf, Alexandre Wagner Silva (Springer Nature, 2019)
Red tilapia is a phenotype with potential value to the tilapia industry due to its attractive skin coloration. However, the presence of black blotches scattered on the body makes these fish less valuable than blemish-free red fish. The correlation between the degree of blotching and other economic traits is important for selective breeding programs including high-performance red fish without black blotches. Therefore, this study aimed to assess the magnitude and direct and indirect effects of blotching in crossbred red tilapia on the growth rate and body measure traits using path analysis methodology. Six genetic groups were evaluated in terms of body measurements, body weight rate, and proportion of black blotching over 250 days of growth: Chitralada and Red-Stirling; crossbred F1—♀ Red-Stirling × ♂ Chitralada and ♀ Chitralada × ♂ Red-Stirling, and the introgressive crossbreeding—♀ CR × ♂ Chitralada and ♀ Chitralada × ♂ CR (C × CR). All variables showed high and positive linear correlations. Individuals with black blotches had lower coefficients of correlation with other variables (body weight and measurements); the direct and indirect effects are near zero. The path analysis indicated a lack of genetic correlation between the degree of black blotches and the economic traits of red tilapia. This facilitates the development of high growth performance red fish with blotched-free reddish skin.
Keywords: Aquaculture; Breeding program; Growth; Oreochromis niloticus; Pigmentation; Red tilapia